A taxonomic revision of the Colombian species of Urosigalphus Ashmead (Hymenoptera: Braconidae) - _, Arias-Penna; Carolina, Diana; Whitfield, James B. (Zootaxa, 2012)
The Colombian species of parasitoid wasp Urosigalphus are revised for the first time, based on specimens deposited inmuseums. Almost all the material was collected by Malaise trap in the understory stratum of the seasonally flooded forest(varzea), submontane forest, and lowland forest, located in protected areas. 23 new species are described and illustrated:U. aliuslongitudinis Arias-Penna, n. sp., U. amandae Arias-Penna, n. sp., U. carinaverticis Arias-Penna, n. sp., U.cavusscuti Arias-Penna, n. sp., U. colombiensis Arias-Penna, n. sp., U. colordissimilis Arias-Penna, n. sp., U.faciescarinae Arias-Penna, n. sp., U. fimbriaeplanae Arias-Penna, n. sp., U. frequens Arias-Penna, n. sp., U. inaequalisArias-Penna, n. sp., U. macarenaensis Arias-Penna, n. sp., U. margo Arias-Penna, n. sp., U. metanotuminsignum Arias-Penna, n. sp., U. monticola Arias-Penna, n. sp., U. notauliremoti Arias-Penna, n. sp., U. ocellivicini Arias-Penna, n. sp.,U. ordoincompositus Arias-Penna, n. sp., U. sharkeyi Arias-Penna, n. sp., U. singularis Arias-Penna, n. sp., U. taniaeArias-Penna, n. sp., U. tredecimantennae Arias-Penna, n. sp., U. triacarinae Arias-Penna, n. sp., and U. whitfieldi AriasPenna, n. sp. An updated key to the known South American species is presented.